Fiqh and Divorce Law in Indonesian Cinema: A Critical Analysis of Talak 3 and Wedding Agreement - Zuhroh, Poetri Lailatuz (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2025)
As a form of popular culture, film serves as an engaging medium for disseminating and popularizing family law in a more appealing and accessible way. However, narrative distortions and misrepresentations of legal norms within cinematic stories are possible. This article examines how the concept of triple divorce in Indonesian Islamic Family Law is portrayed in two Indonesian marriage-themed films: Talak 3 and Wedding Agreement. Both films depict divorce proceedings within the jurisdiction of Indonesia’s Religious Courts. Through a normative legal analysis combined with qualitative content analysis, this study finds that the cinematic depiction of divorce processes in these films is not entirely consistent with the principles of Indonesian Islamic family law. Talak 3 depicts the pronouncement of three divorces at once as constituting an irrevocable major divorce (ṭalāq ba’in kubrā). At the same time, Wedding Agreement portrays consecutive triple divorces occurring outside the court, similarly resulting in an irrevocable major divorce when submitted to the Religious Court. These portrayals tend to reflect classical fiqh doctrines rather than Indonesia’s codified Islamic family law, thereby reinforcing a conservative perspective. Such misrepresentations within Indonesian films risk perpetuating public misunderstandings and undermining efforts to modernize family law. Given the film’s influence in shaping legal awareness, accurate legal depiction in popular media is essential. This study urges scholars and practitioners to ensure that films accurately represent family law, thereby enabling cinema to positively support legal literacy and the progressive development of Indonesian Islamic family law.